2019
DOI: 10.1097/iae.0000000000002276
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension and Optical Coherence Tomography Angiography Features of the Central Macula After Repair of Rhegmatogenous Retinal Detachments

Abstract: Optical coherence tomography angiography demonstrates significant reduction in mean capillary density index and fractal dimension in patients after surgery for RRD in our patients. Thus, reduction in vascular perfusion and branching pattern identified using novel analysis techniques on optical coherence tomography angiography images may provide an insight into the reasons for suboptimal visual gain after RRD surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 20 publications
8
62
2
Order By: Relevance
“…The study of Woo et al 17 included patients with macula-on and macula-off RRD, and, although they measured the healthy fellow eyes as controls, macula-off eyes were compared with the control eyes of both macula-on and macula-off patients. Similar to the study of Agarwal et al, 15 the observed difference could also be due to the interindividual variability of FAZ.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The study of Woo et al 17 included patients with macula-on and macula-off RRD, and, although they measured the healthy fellow eyes as controls, macula-off eyes were compared with the control eyes of both macula-on and macula-off patients. Similar to the study of Agarwal et al, 15 the observed difference could also be due to the interindividual variability of FAZ.…”
Section: Discussionsupporting
confidence: 85%
“…The current literature reports contradicting results regarding the FAZ after surgery for macula-off RRD. One study 19 reported no difference in FAZ between macula-off RRD eyes and control eyes, and two other studies 15,17 reported larger FAZ in macula-off RRD eyes compared with control eyes. These contradicting results can be explained by differences in control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study did not analyze the FAZ area or VD of the eyes with RRD and did not show the specific endotamponade used in vitrectomy. Agarwal et al 16 investigated OCTA features in patients with macula-off RRD who underwent scleral buckling or vitrectomy with gas tamponade and compared them with healthy subjects. They revealed that mean capillary density index were reduced and FAZ area were enlarged in both the SCP and DCP in patients after surgery.…”
Section: Discussionmentioning
confidence: 99%